Determination of SARS-CoV-2 Contamination in a Neonatal Intensive Care Unit (NICU) Environment Using Droplet Digital PCR (ddPCR). (March 2022) - Vayalumkal, J.; Pillai, D.; Oberding, L.; Ward, L.; Fonseca, K.; Mehrem, A. Abou; Conly, J.
Abstract : Purpose: Neonatal infections with SARS-CoV-2 are thought to be less contagious than in older children and adults. The transmission of SARS-CoV-2 from neonates and their environment has not been well studied. Droplet Digital PCR (ddPCR) is an emerging and sensitive technology that can aid infection control investigations. We sought to document surface contamination within the immediate environment of a preterm neonate with congenital COVID-19 using ddPCR. Methods & Materials: On day 5 of life, a total of 23 environmental samples were collected in Eswabs (Amies media) based on proximity to the neonate, from the inside (7) and outside (16) of the neonate's incubator for ddPCR analysis. Samples were extracted, using an in-house method and each extract was run for reverse-transcription ddPCR measurement using the Bio-Rad SARS-CoV-2 ddPCR Kit. The 96-well RT-ddPCR ready plate was loaded into the QX200 Droplet Reader (Bio-Rad, Pleasanton, CA). The fluorescence intensity of each droplet was measured, and droplets were determined to be positive or negative for gene targets (N1, N2). Results: All samples collected from outside of the incubator were negative.These included: a stethoscope hanging outside of the incubator, nearby keyboard/mouse, wireless phone receiver, barcode scanner, blood culture bottles, pens/pencils, light switches, weigh scale, countertop/shelf, cart with drawers and incubator port release clips. Samples collected from inside the incubator were positive for SARS-CoV-2. These results reported in copies per microlitre (cp/µL) extract included: the swaddle cloth (0.4 N2), sheets behind the neonate's head (11.4 N1, 16.9 N2), cardiorespiratory and saturation monitor leads and cables near the neonate's head (2.8 N1, 4.5 N2), near the neonate's feet (2.1 N1, 3.7 N2), and nametags hanging on a panel (1.0 N1, 1.2 N2). The highest levels were noted from the neonate's drool (25.2 N1, 35.2 N2). Conclusion: The presence of SARS-CoV-2 was confirmed by ddPCR in environmental samples inside the incubator confirming the ability of the neonate to spread the virus in close quarters. No virus was identified outside of the incubator which suggests appropriate hand hygiene and disinfection of environmental surfaces. ddPCR appears to be a useful tool for investigating the potential role of fomites in COVID-19 transmission